The search for a peptide ligand targeting the lipolytic enzyme cutinase - Breccia, Javier Dario (2003)
A constrained nonapeptide phage display library was evaluated as a potential source of affinity ligand(s) for purification of cutinase, a lipolytic enzyme. After seven cycles of biopanning, 500 clones were isolated and individually tested for their capability to interact with cutinase. Three out of six sequenced clones carrying a cutinase-specific constrained peptide showed the same insert sequence (CRLHHWRYC). Sequences of two of the other clones highlighted a LXXW motif as a critical determinant in the make-up of a cutinase-specific sequence. Although the affinity of the most commonly found peptide for cutinase is low, we suggest that LXXW motif may be a suitable starting point in the development of affinity peptides suitable for use in the study and purification of cutinase.